Prosthetic Implications Of Dental Anomalies - RITHANYA, M.; KOMMI, VENKATESH; SASHANK, KEERTHI; BRUNDHA, M.P. (The journal of contemporary issues in business and government, 2021)
This paper is aimed to describe a number of dental anomalies which every dental practitioner of all discipline will be destined to encounter. The dental anomalies, how it affects the particular prosthetic implications and what could be done for treatment, if alterations could be done in the prosthetic implications are discussed in this review article.A number of articles around 40 were collected from search engines like PubMed , scholar and so much more.The articles were thoroughly reviewed to write this article on Dental Anomalies affecting prosthetic implications. Dental anomalies are the abnormalities present in the teeth and oral cavity. Dental anomalies are a wide range of disorders comprising various disorders of the teeth into the categories : acquired abnormalities and developmental abnormalities.. Developmental anomalies are divided into five groups for classification. They are abnormalities in size, number, morphology, shape and the location of the tooth. The teeth number anomalies are hypodontia, hyperdontia. In these abnormalities there will be less number of teeth and increased number of teeth respectively. We also have positional anomalies which include transposition. Morphological anomalies include Concrescence, fusion and gemination( double teeth).The other abnormalities are taurodontism, dilaceration including supernumerary roots, Dens Evaginatus and Dens Invaginatus. Structural anomalies include Dentinogenesis Imperfecta and Amelogenesis Imperfecta. Tooth impaction is also one of the developmental anomalies seen. Acquired tooth disorders include tooth ankylosis, resorption. Hypercementosis, pulpstone, tooth fluorosis, abrasion, erosion, Syphilitic Hypoplasia, molar incisor hypo mineralisation are some of the other acquired dental anomalies.